PEMANFAATAN PUPUK BIO-SLURRY PADA JENIS TANAH YANG BERBEDA TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT DI PRE-NURSERY - Pauliz Budi Hastuti; Surya Budi Setiawan (Program Studi Agroteknologi INSTIPER, 2017)
The aim of this research was to determine the effect of Bio-slurry fertilizer on various types of soil to the growth of oil palm seedlings in pre-nursery. Factorial completely randomized design was used in this research. The first factor was the kind of soil, which consists of two levels: latosols and regosols. The second factor was the dose of Bio-slurry fertilizer consisting of four levels : 50 ml tan-1 , 100 ml tan-1 , and 150 ml tan-1 and standard fertilizers dosage (NPKMg and Urea) as a control. The results showed that Bio-slurry fertilizer can replace the role of inorganic fertilizer in spurring the growth of oil palm seedlings in pre-nursery. Regusols provides better growth of palm seedlings than latosols.